Implementasi Algoritma Binary Space Partitioning Untuk Procedural Map Generation Dalam Gim - Rosyid, Harits Ar; Prasetyo, Ahmad Adi (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
The popularity of games as an interactive entertainment medium continues to grow, with 2D maps playing a vital role in enhancing user experience. Manual map creation is time-intensive, particularly as game worlds become increasingly complex. Procedural Content Generation (PCG) offers a solution by automating map creation, improving replayability, and reducing designer workload. This research explores the use of the Binary Space Partitioning (BSP) algorithm for procedural dungeon map generation, incorporating random connections between rooms to create more exploratory and dynamic maps. The process includes three stages: developing a dungeon map generator, implementing BSP with random room connectors, and validating the generated maps to ensure navigability. Space Syntax analysis, including Visibility Graph Analysis (VGA) and Axial Line Analysis, is applied to evaluate the quality of the maps in terms of connectivity, visibility, and integration. Results show that BSP-generated maps with random connections offer dynamic layouts, while Space Syntax measures reveal that smaller minimum room sizes result in lower integration and connectivity but increase interaction hotspots. This study demonstrates the potential of BSP in generating varied game maps and the utility of Space Syntax for assessing their spatial properties.